Exploring the postsecular : the religious, the political and the urban - Molendijk, Arie L.; Beaumont, Justin.; Jedan, Christoph. (International Studies in Religion and Society, 2010)
The re-emergence of the religious in secular domains has led prominent scholars such as Jürgen Habermas and Charles Taylor to speculate about a new 'postsecular' age. The alleged shift from the secular to the postsecular is most visible in the spheres of urban public space, governance and civil society. This volume addresses contemporary relations between religion, politics and urban societies primarily from a theoretical perspective, while also paying attention to empirical manifestations of the central conceptual ideas. The primary focus is the relations between public religion, deprivatization of religion and theorizations of modernity and modernities, with the secondary and closely related focus on theorizing postsecular urbanism including the role of faith based organizations (FBOs) in cities.